Efficient treatment of actual pharmaceutical wastewater by wet oxidation process in subcritical water apparatus - Ahmad, U.; Pu, Y.; Qi, W.; Foster, Neil; Chen, J.; Wang, D. (Wiley-Blackwell Publishing, 2017)
© 2017 Canadian Society for Chemical Engineering Pharmaceutical wastewater is a typical persistent refractory organic industrial wastewater. In this work, a simple, one-step method for the treatment of pharmaceutical wastewater was developed using wet oxidation (WO) in a subcritical water apparatus, with detailed studies on the effects of operating parameters, including the temperature of the system, the ratio of reactants, and pH of the wastewater. Under optimized experimental conditions, efficient treatment of actual pharmaceutical wastewater was achieved, with removal of 100 % chemical oxygen demand (COD), 98 % nitrate ion, 98 % nitrite ion, and 68 % ammonium ion. Our results suggest that the WO process, using a subcritical water apparatus, is a promising method of treatment for pharmaceutical wastewater.